PENGARUH TERPAAN INFORMASI DI MEDIA DIGITAL DALAM MEMBENTUK NIAT MELAKUKAN HEALTHY DIET (Analisis Model Pengembangan dari Theory of Planned Behavior dalam Konteks Komunikasi Penerapan Healthy Diet Pada Orang Dewasa) - Sasita Dewi Andini; S. Rouli Manalu (Interaksi Online, 2026)
The increasing use of digital media in Indonesia as a primary source of health information encourages greater exposure to content about healthy lifestyles and balanced nutrition. People are increasingly actively seeking and consuming information related to healthy diets, but the increasing prevalence of obesity indicates a gap between information exposure and actual behavior in adopting a healthy lifestyle. This study aims to analyze the influence of information exposure in digital media on attitudes, as well as the influence of attitudes, subjective norms, and behavioral control on the intention to adopt a healthy diet in adults in Indonesia. In addition, this study also examines the role of attitude as a mediating variable between information exposure and the intention to adopt a healthy diet. The theory used in this study is the Theory of Planned Behavior. This study uses a quantitative approach with a non-probability sampling technique. Hypothesis testing is carried out using Partial Least Squares (PLS-SEM) analysis. The results of the study showed that exposure to information in digital media had a very significant effect on attitudes, with path coefficients of 0.414, P-values of 0.000 (<0.001), T-statistics of 6.674 (>1.96), and had a medium effect (f² = 0.207). Furthermore, attitudes had a very significant effect on the intention to do a healthy diet, with path coefficients of 0.409, P-values of 0.000 (<0.001), T-statistics of 5.372 (>1.96), and had a medium effect (f² = 0.245). Subjective norms had a significant effect on the intention to do a healthy diet, with path coefficients of 0.126, P-values of 0.014 (<0.05), T-statistics of 2.452 (>1.96), and had a small effect (f² = 0.030). Behavioral control has a very significant effect on the intention to do a healthy diet, with path coefficients of 0.359, P-values of 0.000 (<0.001), T- statistics of 5.787 (>1.96), and has a medium effect (f² = 0.191). In addition, the results of the study also show that attitudes significantly mediate the relationship between exposure to information in digital media and the intention to do a healthy diet with path coefficients of 0.169, P-values of 0.000 (<0.001) and T-statistics of 4.063 (>1.96). The coefficient of determination (R Square) shows that information exposure explains 17.1% of the variance in attitudes (R² = 0.171), while attitudes, subjective norms, and behavioral control simultaneously explain 49.7% of the variance in the intention to do a healthy diet (R² = 0.497). Therefore, all hypotheses in this study are accepted and the research findings are in line with the theory used, where behavioral intentions are predicted by attitudes, subjective norms, and behavioral control, and can be strengthened by additional predictors in the form of exposure to information in digital media.